Language Policy of Bilingual Family Towards Children’s Word Production - Ira Maria Fran Lumbanbatu; Sumarsih Sumarsih; Lince Sihombing (LINGUISTIK TERAPAN, 2015)
The objectives of this study are to investigate the way the bilingual families decide their own language policy through the components of language policy, the way the parents apply language policy to succeed their children words production, and to find out the factors why the parents apply the language policy the way they are. This research applied qualitative approach by phenomenology term through observation, questionnaire and in–depth interview. The research findings showed that bilingual families use the components of language policy namely language ideology, language practice and language management. Mostly parents considered language ideology and language management. Otherwise, language practice were not applied by them completely, it can be seen through language that their children use will be different with what the parents have expected. Language policy is applied in family by practicing the language directly. There are some influences that make the parents practice the language directly, namely: influences of outside home and there is no balance guidance of practicing language between mother and father. Factors that support parents in conducting language policy are intermarriage, maintaining the language particularly tribal language, the position of language using in formal context such as school and the position of language which is used in their environment.   Keywords: Bilingual families; Language policy; and Word Production.